An Archetypal Graphic Model in the Conics of Apollonius (diségno, 2024)
In the ancient world, and therefore well before the codification of the double orthogonal projection method developed by Gaspard Monge [Monge 1799], it was possible to represent three-dimensional space as faithfully as methods of a projective nature allow today. These representations, while not being documented by means of graphics, are in fact documented thanks to the descriptions obtained from texts, such as that of the Conics of Apollonius of Perga. [read more]